2015
DOI: 10.1038/srep09613
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-driven lipid accumulation and dendritic cell dysfunction in cancer

Abstract: Dendritic cells (DCs) play important roles in the initiation and maintenance of the immune response. The dysfunction of DCs contributes to tumor evasion and growth. Here we report our findings on the dysfunction of DCs in radiation-induced thymic lymphomas, and the up-regulation of the expression of the lipoprotein lipase (LPL) and the fatty acid binding protein (FABP4), and the level of triacylglycerol (TAG) in serum after total body irradiation, which contribute to DCs lipid accumulation. DCs with high lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 32 publications
2
48
0
1
Order By: Relevance
“…These DCs exhibited endoplasmic reticulum (ER) stress and robust activation of an ER stress response factor spliced X-box-binding protein 1, which induced triglyceride biosynthesis leading to abnormal lipid accumulation. Other recent studies confirmed that dysfunction of DCs in radiation-induced thymic lymphoma and mesothelioma was mainly due to lipid accumulation [78, 79] (Fig. 2).…”
Section: Dysfunction In Cancersupporting
confidence: 65%
“…These DCs exhibited endoplasmic reticulum (ER) stress and robust activation of an ER stress response factor spliced X-box-binding protein 1, which induced triglyceride biosynthesis leading to abnormal lipid accumulation. Other recent studies confirmed that dysfunction of DCs in radiation-induced thymic lymphoma and mesothelioma was mainly due to lipid accumulation [78, 79] (Fig. 2).…”
Section: Dysfunction In Cancersupporting
confidence: 65%
“…Some authors demonstrate in cancer models an opposite correlation between LD induction and Ag presentation. It was observed in murine lymphoma that lipid‐enriched dendritic cells are not able to induce CD4 T cell proliferation by the reduction in the expression of co‐stimulatory molecules and in cytokine production (IL‐12, IL‐1, and IFN‐γ) . Accordingly, it was also demonstrated that lipid‐enriched dendritic cells from tumor‐bearing mice have a reduced capacity to process and present Ags to T cells, displaying a tolerogenic phenotype.…”
Section: Lds and Antigen Presentationmentioning
confidence: 99%
“…More recently, an increase in the number of LDs in dendritic cells has been described during infection by Leishmania amazonensis or Nocardia brasiliensis and cancer. 185,[195][196][197] LDs have been described to interact with several organelles and structures within cells, including phagosomes, 91 autophagosomes, and the proteasome. 12 These results suggested that these lipid-rich organelles could be involved in cellular processes related to Ag presentation and immunity.…”
Section: Lds and Antigen Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…DC vaccines emerged in an effort to avoid possible interference with therapeutic efficacy due to the dysfunction of endogenous DCs, which were commonly observed in cancer patients (20,21). However, it is important that the DCs used in these vaccines are presented in a 'mature' state to activate an antigen-specific immune response upon T-cell encounter.…”
Section: Discussionmentioning
confidence: 99%